Application of Cold Packs to Reduce Pain and Hematoma After Percutaneous Coronary Intervention Procedures in Posterior Stenosis Patients: A Case Study - Nur Asnah Sitohang; Santi Sihombing (GLOBAL HEALTH SCIENCE GROUP, 2025)
Percutaneous coronary intervention (PCI) is the standard reperfusion therapy in ST-Elevation Myocardial Infarction (STEMI) patients, but local complications such as pain and hematoma in the access area, especially femoral access, are still common. Non-pharmacological interventions in the form of cold packs are known to have benefits in reducing inflammation and reducing hematoma formation through local vasoconstriction mechanisms. This study aims to describe the application of cold packs in reducing pain and hematoma in posterior STEMI patients after PCI procedures. Method: This study used a single-case design on a 58-year-old female patient post-PCI through femoral access at Haji Adam Malik Hospital Medan. The cold pack intervention was wrapped in a towel or sterile gauze and applied for 15-20 minutes with the patient in a supine position. Pain assessment was performed using the Numeric Rating Scale (NRS), while hematoma was evaluated through diameter and skin discoloration. Monitoring was done before and after the intervention and for three days. There was a significant reduction in pain from NRS 5 to 1-2 and hematoma shrinkage from ±5 cm to ±2 cm without active bleeding or side effects. Cold pack is effective, safe, and easy to apply as a nursing intervention in reducing pain and hematoma post-PCI. Cold packs are recommended as a nonpharmacologic nursing intervention that can reduce pain and hematoma post-PCI.